Kegiatan Sosialisasi Dampak Gadget Terhadap Anak di Desa Gung Pinto Kec. Naman Teran, Kab. Karo - Siregar, Siti Julianita; Meri Sri Wahyuni; Kamil Erwansyah; Azlan (Cattleya Darmaya Fortuna, 2025)
Gadgets are electronic devices with practical functions, have special features and functions to make human work easier. In today's technological developments, the use of gadgets has increased significantly. The use of gadgets such as smartphones and tablets has become an inseparable part of children's daily lives where the use of gadgets can make it easier for children to access information, entertainment, and social interaction in their grasp. Excessive use of gadgets can have negative impacts on children such as sleep disorders, decreased quality of social interaction, addiction, stress, anxiety and aggressive behavior. Therefore, a community service activity was held in Gung Pinto Village, Namanteran District, Karo Regency. This community service activity was carried out using counseling and socialization methods for children. The purpose of this community service activity is to increase public awareness, especially parents, about the impact of gadget use on children. It is hoped that parents will better understand the risks and impacts of using these gadgets and be able to take the necessary precautions to reduce these negative impacts. In addition, this activity also aims to teach children about the importance of understanding how to reduce gadget use.